THE DIVERSITY OF METHODOLOGIES APPLIED IN INDONESIAN JOURNAL ARTICLES FOCUSED ON BIOCHEMISTRY LEARNING - Wahyono, Poncojari; Wardiani, Fefi Eka; Susetyarini, Eko (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Biochemistry is a study which consists of many difficult concepts. Research that examines biochemistry learning needs to be continuously carried out so that the quality of learning can be evaluated and improved. Hence, this content analysis addressed to analyze the research methodologies of the articles published in various Indonesian biology education journals. The focus of the articles studied was biochemistry learning in Indonesia. To go further, the articles must be published between 2000 and 2020. The findings of this study informed that during the last two decades, the research publications which examined biochemistry learning have rarely been carried out. From those publications, quantitative research was the research type used the most. In addition, postgraduate student was the most frequently chosen as the research subject. Furthermore, questionnaire sheet was the highest preference of data collection instrument used. Meanwhile, the highest frequency of data analysis methods used were percentage and N-gain calculation. The low number of publications and the lack of research methodology diversity need to be more seriously considered by increasing the number of studies examining biochemistry learning in Indonesia.